2016
DOI: 10.1021/acs.cgd.5b01568
|View full text |Cite
|
Sign up to set email alerts
|

Initial Report on Molecular and Electronic Structure of Spherical Multiferrocenyl/tin(IV) (Hydr)oxide [(FcSn)12O14(OH)6]X2 Clusters

Abstract: Two spherical organic−inorganic ferrocene-tin (hydr)oxide clusters of general formula [(FcSn) 12 O 14 (OH) 6 ]X 2 (Fc = ferrocenyl, X = nitroso-dicyanmethanide, DCO − and benzoylcyanoxime, PCO − anions) were prepared by the direct hydrolysis of Fc 2 SnCl 2 or FcSnCl 3 precursors in the presence of light-and thermally stable Ag(DCO) or Ag(PCO) salts. Molecular structures of FcSnCl 3 Py 2 (1), Fc 2 SnCl 2 Py 2 (2), [(FcSn) 12 O 14 (OH) 6 ](DCO) 2 (3), and [(FcSn) 12 O 14 (OH) 6 ](PCO) 2 (4) were investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 136 publications
(176 reference statements)
1
1
0
1
Order By: Relevance
“…In conclusion we have shown that simple tripod‐type diorganotin halides such as MeSi(CH 2 SnRI 2 ) 3 (R=Ph, Me 3 SiCH 2 ) serve as precursors for the synthesis of novel belt‐shaped molecular diorganotin oxides [MeSi(CH 2 SnRO) 3 ] n of unprecedented oktokaideka ( n =18) and trikonta ( n =30) nuclearity. The results obtained fit well into the ongoing interest in large‐sized metaloxido clusters in general [2k] and tinoxido clusters of high nuclearity in particular [5g, 6b, 12, 31, 32] . The concept shown herein holds great potential for future work and we encourage interested readers to step into the field.…”
Section: Resultssupporting
confidence: 77%
“…In conclusion we have shown that simple tripod‐type diorganotin halides such as MeSi(CH 2 SnRI 2 ) 3 (R=Ph, Me 3 SiCH 2 ) serve as precursors for the synthesis of novel belt‐shaped molecular diorganotin oxides [MeSi(CH 2 SnRO) 3 ] n of unprecedented oktokaideka ( n =18) and trikonta ( n =30) nuclearity. The results obtained fit well into the ongoing interest in large‐sized metaloxido clusters in general [2k] and tinoxido clusters of high nuclearity in particular [5g, 6b, 12, 31, 32] . The concept shown herein holds great potential for future work and we encourage interested readers to step into the field.…”
Section: Resultssupporting
confidence: 77%
“…The most symmetrical Sn 12 O x structure is that of the cationic cluster [R 12 Sn 12 O 14 (OH) 6 ] 2 + (R=iPr, [37] Bu, [19,38] CH 2 Ph, [39] CH 2 SiMe 3 , [40] ferrocenyl). [41] The Sn atoms form a distorted icosahedron, whereof 14 of the 20 triangular faces are capped by μ 3 -O. An alternative description is that the structure consists of a central layer of six edge-sharing [RSnO 4 ] square pyramids and a top and bottom layer of three edge-sharing [RSnO 5 ] octahedra.…”
Section: Cage Compoundsmentioning
confidence: 99%
“…The most symmetrical Sn 12 O x structure is that of the cationic cluster [R 12 Sn 12 O 14 (OH) 6 ] 2+ (R= i Pr, [37] Bu, [19,38] CH 2 Ph, [39] CH 2 SiMe 3 , [40] ferrocenyl) [41] . The Sn atoms form a distorted icosahedron, whereof 14 of the 20 triangular faces are capped by μ 3 ‐O.…”
Section: Tin Oxo Clusters With Nuclearities ≥12mentioning
confidence: 99%
“…Zusammenfassend haben wir gezeigt, dass einfache Dreifuß‐Typ Diorganozinnhalogenide wie MeSi(CH 2 SnRI 2 ) 3 (R=Ph, Me 3 SiCH 2 ) als Edukte für die Synthese neuartiger gürtelförmiger molekularer Diorganozinnoxide [MeSi(CH 2 SnRO) 3 ] n von bisher beispielloser oktokaideka ( n =18) und trikonta ( n =30) Nuklearität dienen. Die erhaltenen Resultate liegen im andauernden Interesse an großformatigen Metalloxoclustern im Allgemeinen [2k] und Zinnoxoclustern hoher Nuklearität im Speziellen [5g, 6b, 12, 31, 32] . Das hier vorgestellte Konzept besitzt großes Potenzial für zukünftige Arbeiten und wir ermutigen interessierte Leser es aufzugreifen.…”
Section: Zusammenfassung Und Ausblickunclassified